Fibrosis Progression and Incidence of Cirrhosis and Hepatic Decompensation in Persons Treated with Paritaprevir/Ritonavir/Ombitasvir/Dasabuvir: Results from ERCHIVES. (4th October 2017) - Simon, Tracey; Yan, Peng; Kort, Jens; Butt, Adeel
Abstract: Background: Data are limited regarding the effect of paritaprevir/ritonavir, ombitasvir, dasabuvir regimen (PrOD) upon the rate of liver fibrosis progression and incidence of cirrhosis and hepatic decompensation after treatment for HCV. Methods: Within ERCHIVES (Electronically Retrieved Cohort of HCV Infected Veterans), we identified HCV infected persons treated with PrOD and treatment-nave controls to determine the effect of PrOD treatment upon subsequent progression of fibrosis and incident cirrhosis and hepatic decompensation. Controls were propensity-score matched based on demographic and clinical characteristics. We excluded those with HIV coinfection, positive HBsAg, hepatocellular carcinoma at baseline and those with missing HCV RNA or FIB-4 scores. Fibrosis progression and liver cirrhosis were assessed using the FIB-4 score. Results: The final propensity score matched sample included 1, 473 PrOD-treated individuals, and an equal number of matched, untreated controls. PrOD-treated patients had significantly reduced median FIB-4 scores over time, compared with controls (median absolute change in FIB-4 = -0.7 [IQR -1.51, -0.3] vs. +0.06 [IQR -0.38, 0.49]; P < 0.0001). Compared with matched controls, PrOD-treated patients had an 86% relative reduction in the risk of incident cirrhosis over 2, 241 patient-years of follow-up (adjusted HR 0.14 [95% CI 0.08-0.23]). Treatment with PrOD was also associated with delayed time to first hepatic decompensation event ( P < 0.001). In sensitivity analysis, the exclusion of patients with baseline cirrhosis did not materially alter the estimates of effect. Conclusion: Treatment with PrOD is associated with a significant reduction in fibrosis progression, a longer time to the development of cirrhosis, and reduced risk of hepatic decompensation. Our results demonstrate the long-term anti-fibrotic benefits associated with PrOD therapy for chronic HCV. Disclosures: J. Kort, Abbvie: Employee and Shareholder, Salary; A. Butt, Merck: Investigator, Grant recipient